Anticipation in conference interpreting: a cognitive process - Vandepitte, Sonia (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2001)
In conference interpretation research, anticipation is usually seen as the oral production of a particular part of a message in special circumstances. In psychophysiological research, however, anticipation is a mental process. The article presents a revised definition of anticipation that takes account of both approaches. It does so in terms of deliberate enrichment, a conceptual tool from relevance theory. Anticipation in conference interpreting is found to yield a high number of strengthenings rather than deletions, additions or contextual implications. This is a cognitive aspect which is typical of interpreting and distinguishes it from other communication events.